Differences in the main composition and molecular components of sheep and cow butter oils produced by the local traditional method - Dasht Peyma, Atefeh; Piravi Vanak, Zahra; Ghavami, Mehrdad (Frontiers in Food Science and Technology, 2022)
Sheep and cow butter oils have high consumption and trade rate in the market, but standards regarding type differentiation is lacking. Therefore, the objective of this study was to assess the distinction of main and molecular components of sheep and cow butter oils. Sanjabi sheep and Holstein cow butters were produced from milk collected in two seasons of summer and autumn via conventional local method. The main components including fatty acids, triacylglycerols, sterol composition and PCR test for evaluation of molecular components were determined in butter oil samples. The most significant differences in fatty acids were for C10:0 and C16:0, and regarding TAGs were for C40, C42, C48, and C50 in sheep butter oils of two seasons. The sterol composition in cow and sheep butter oils was similar but had differences in the two seasons. PCR tests also showed that cow and sheep butter oils differ in molecular components. It can be concluded that it is possible to differentiate these two oils using triacylglycerols, fatty acids and molecular evaluation.